Analysis of Tuberculosis Diagnosis Methods in Children: A Literature Review - Qonita Abdillah Rosyida; Fahma, Hilmia (Journal of Diverse Medical Research: Medicosphere, 2024)
Abstract Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis. According to the World Health Organization (Global TB Report, 2023), TB is still a health problem in the world today. The number of people newly diagnosed with TB globally will be 7.5 million in 2022, with 12% being children (aged 0–14 years). One of the main focuses in treating TB is knowing the correct diagnosis method. TB examination in children is usually carried out by taking a Rapid Molecular Test (TCM) sputum specimen. However, sometimes this method is less effective because the child has difficulty expelling phlegm spontaneously. To overcome this problem, various countries have implemented other TB diagnosis methods such as Stool Culture, Xpert, and Xpert Ultra diagnosis. The Xpert diagnosis method increases the sensitivity of Mycobacterium tuberculosis detection so that TB detection in children can be more accurate. In the future, the Xpert Ultra diagnostic method has begun to be developed, whose sensitivity is more accurate than the Xpert method. With the correct diagnostic method, it is hoped that the treatment process for children with TB can be more effective.